تقييم أداء المصارف التجارية الليبية الخاصة باستخدام معايير التقييم الدولية - د. أحمد بلقاسم تواتي (Aljameai, 2022)
الملخص:هدفت الدراسة إلى تقييم أداء لمصارف التجارية الليبية الخاصة باستخدام معيار CAMELS الدولي والمعتمد بنظام التقييم المصرفي الأمريكي ومدى ملائمة هذا المعيار للبيئة المصرفية الليبية. حيث يعتمد هذا المعيار على تقييم أداء المصارف باستخدام ستة مؤشرات وهي: كفاية رأس المال، وجودة الأصول، وجودة الإدارة، والربحية، والسيولة، وحساسية أصول المصرف لمخاطر السوق. حيث تمحورت إشكالية البحث حول هذه المؤشرات ومدى قدرتها على تقييم أداء المصارف التجارية الليبية الخاصة، واعتمد البحث على تحليل بعض بنود القوائم المالية المستخدمة في مؤشرات المعيار ومقارنتها بنسب المعيار لتحديد النتائج، وقد تمثلت عينة الدراسة في مصرف المتحد للتجارة والاستثمار، ومصرف الواحة خلال الفترة (2014-2017). وقد توصلت الدراسة إلى عدة نتائج أهمها: عدم ملائمة تطبيق كامل مكونات المؤشر في المصارف التجارية الليبية الخاصة بسبب تعذر تقييم عنصر حساسية السوق لعدم توفر البيانات المطلوبة، وبالتالي تم تطبيق الصيغة الثانية للمؤشر وهو معيار CAMEL إلا أن مؤشرات معيارCAMELS أسهمت في تقييم أداء المصارف التجارية الليبية الخاصة، فيما يخص باقي مكونات النموذج.Abstract:The study aimed to evaluate the performance of private Libyan commercial banks using the CAMELS Index approved by the American banking evaluation system the suitability of this indicator for the Libyan banking environment. As this indicator is based on evaluating the performance of banks from several aspects, including capital adequacy, asset quality, management, profitability, liquidity, and market sensitivity. The research problem centered around these indicators and their ability to evaluate the performance of private Libyan commercial banks. The research relied on analyzing some of the financial statement’s items used in the index equations and comparing them with the index ratios to determine the results. The study sample included two private banks: The United Bank for Commerce & Investment and the Alwaha Bank. During the period (2014-2017). The study reached several results, the most important of which are: The inadequacy of the application of all components of the index in private Libyan commercial banks due to the unavailability of some model data, as it was not possible to assess the market sensitivity element due to the lack of required data. Therefore, the second version of index, which is CAMEL standard, was applied. It contributed to evaluating the performance of private Libyan commercial banks, with regard to the remaining components of the model.